THE IMPACT OF THE EXECUTION ON THE OBJECT FIDUCIARY GUARANTEE - Ikhsan, Muhammad; Aisyah, Siti (SYNTIFIC, 2023)
Background. Guarantees in the broadest sense are guarantees of a material or immaterial nature. Material collateral for example buildings, land, vehicles, jewelry, securities. Meanwhile, immaterial guarantees include individual guarantees (borgtocht). Fiduciary is the transfer of ownership rights to an object based on trust with the condition that the object whose ownership rights are transferred remains in the control of the owner of the object.. The research purpose describes the impact of the execution on the object fiduciary guarantee. Research Method. This research used Normative Juridical research methods, namely research based on studies literature and based on the general explanation of Article 29 of Law Number 42 of 1999 regarding fiduciary guarantees. Findings. If the debtor or fiduciary breaches his promise, then it will the execution of the fiduciary guarantee object is carried out, this is because the fiduciary recipient has the same executorial rights as court decisions that have obtained legal force remains on the object of fiduciary guarantee based on the fiduciary guarantee certificate. Conclusion. The Fiduciary Guarantee Law, in line with Pacta Sunt Servanda, allows for the transfer of ownership rights to an object based on trust.